The Teaching of “Jñana Sandi” in The Text “Tutur Muladara” - I Nengah Lestawi (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
Lontar is a written media which is used in the earlier period before the discovery of the paper as a part of the renewable technology. Studying or researching old manuscripts is not an effortless job. In addition to the technical factors, it also involves language and script which are applied in the text as well as other factors associated with the culture system. In the manuscript, there are texts which match its soul. One text that is fascinating to observe further is the text of Tutur Muladara, the teachings of the spiritual that focus on the integration of sound, breath, and mind. This article analyzes the teachings contained in the text Tutur Muladara. In this text, there are various teachings of kadiatmikan. One of them is the teachings of Jñana Sandhi. This sort of teaching consists of three subs, namely the teaching of seven holes of the sky, Yoga Sandhi and Sang Hyang Adnyana Sandhi